Molecular imaging of water binding state and diffusion in breast cancer using diffuse optical spectroscopy and diffusion weighted MRI - Chung, So Hyun (Society of Photo-Optical Instrumentation Engineers, 2012)
Tissue water content and molecular microenvironment can provide important intrinsic contrast for cancer imaging. In this work, we examine the relationship between water optical spectroscopic features related to binding state and magnetic resonance imaging (MRI)-measured water diffusion dynamics. Broadband diffuse optical spectroscopic imaging (DOSI) and MR images were obtained from eight patients with locally-advanced infiltrating ductal carcinomas ([Formula: see text]). A DOSI-derived bound water index (BWI) was compared to the apparent diffusion coefficient (ADC) of diffusion weighted (DW) MRI. BWI and ADC were positively correlated ([Formula: see text] , [Formula: see text]) and BWI and ADC both decreased as the bulk water content increased ([Formula: see text] and [Formula: see text] , respectively). BWI correlated inversely with tumor size ([Formula: see text] , [Formula: see text]). Our results suggest underlying sensitivity differences between BWI and ADC to water in different tissue compartments (e.g., extracellular vs cellular). These data highlight the potential complementary role of DOSI and DW-MRI in providing detailed information on the molecular disposition of water in breast tumors. Because DOSI is a portable technology that can be used at the bedside, BWI may provide a low-cost measure of tissue water properties related to breast cancer biology.